Case Report: A rare case of mixed epithelial and stromal tumor of the kidney in an adolescent: imaging findings and literature review - Fu, Guang; Xiao, Rong; Yang, Xudan; Lu, Tao (Frontiers in Pediatrics, 2025)
Mixed epithelial and stromal tumor of the kidney (MESTK) is an unusual biphasic benign renal neoplasm. It predominantly occurs in perimenopausal women, with only eight cases reported in children. Owing to its rarity, only limited radiological information has been reported in the literature, in none of the previous pediatric cases were both CT and MRI findings of the tumor provided. Herein, we report a rare case of MESTK in a 13-year-old girl. This case was the largest observed in children to date. Findings from our report provide novel insights into the MRI features of a large pediatric MESTK and indicate the importance of MRI for observing adipose components and the absence of diffusion restriction within the tumor. Radiologists should consider the possibility of MESTK in children when they observe a large, solid renal tumor without diffusion restriction in children.